Gandhian Principles of Swadeshi and Self-Reliance in Nurturing Creative Work: Lessons from Women’s Artisan Movements in the Thar Desert - Bhakhara, Ram (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Postcolonial India saw a dynamic interplay between Mahatma Gandhi’s economic vision of Swadeshi (local self-sufficiency) and the realities of nation-building. This paper examines how Gandhian principles of Swadeshi and self-reliance were transmitted and adapted through women-led artisan movements in the Thar Desert of Western Rajasthan from the 1950s to the 2000s. It highlights “creative work” – traditional crafts and handloom – as a form of localized economic autonomy that empowered marginalized desert communities, especially women. Using a historical research approach, the study draws on Gandhi’s writings, government reports, NGO archives (e.g. URMUL Trust, SURE), and scholarly analyses to trace the emergence, evolution, and impact of these movements. It finds that rural women artisans, inspired (directly or indirectly) by Gandhian ideas, built cooperative enterprises that revived traditional crafts, provided livelihoods, and fostered social agency. The results reveal patterns of feminized Gandhian praxis: small-scale, home-grown industries that balanced village swaraj (self-rule) with pragmatic market engagement. The discussion interprets these findings in terms of “feminized Gandhianism,” the tension between Swadeshi ideals and market forces, contributions to national development goals, and the long-term legacy of these movements. Ultimately, the paper argues that the Thar Desert’s women artisan collectives offer a historically grounded model of sustainable, inclusive development anchored in cultural creativity and self-reliance.